STUDENTS’ WRITING ABILITY PREDICTION THROUGH GRAMMAR MASTERY - Yocha Falentina Helmy (English Language Teaching and Research, 2018)
Grammar mastery and writing ability cannot be separated each other. Both support one another.  This article was intended to see the correlation between grammar mastery and students’ writing ability. The design was quantitative research. The population of the research was all second year regular students of English Department of Universitas Negeri Padang registered in 2007/2008 academic year. The sample was chosen based on cluster sampling technique.  The data was in form of documenter data and analyzed by using Pearson Product Moment. The result showed that “there is positive correlation between grammar mastery and students’ writing ability’ was accepted. It indicates that the ability of the students in writing could be predicted through their grammar mastery.Key words:  correlation, grammar mastery, writing ability